Modulation of dendritic cell and T cell cross-talk during aging: The potential role of checkpoint inhibitory molecules - Gardner, J.; Mamotte, Cyril; Jackaman, Connie; Nelson, Delia (2017)
© 2017 Elsevier B.V. Dendritic cells (DCs) undergo continuous changes throughout life, and there is evidence that elderly DCs have a reduced capacity to stimulate T cells, which may contribute to impaired anti-tumour immune responses in elderly people with cancer. Changes in checkpoint inhibitory molecules/pathways during aging may be one mechanism that impairs the ability of elderly DCs to activate T cells. However, little is currently known regarding the combined effects of aging and cancer on DC and T cell inhibitory molecules/pathways. In this review, we discuss our current understanding of the influence of aging and cancer on key DC and T cell inhibitory molecules/pathways, the potential underlying cellular and molecular mechanisms contributing to their modulation, and the possibility of therapeutically targeting inhibitory molecules in elderly cancer patients.